The Effect of Repetition and Duration Based Circuit Training on Body Mass Index and Physical Fitness Levels among Students - Jamaludin Yusuf; Gilang Nuari Panggraita; Pandu Kresnapati; Wahyu Eko Widiyanto; Willy Ihsan Rizkyanto (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The findings from field observations show that out of the 61 students sampled at SMK Pelayaran Baruna Pemalang, 35 students have a Body Mass Index (BMI) within the normal (healthy) category. Meanwhile, the students’ overall physical fitness level is categorized as low, with 46 students included in this group. This research seeks to examine the influence of repetition-based and duration-based circuit training methods on the BMI and fitness levels of students at SMK Pelayaran Baruna Pemalang. The study utilized an experimental approach with a 2x2 factorial design and was evaluated using Multivariate Analysis of Variance. The independent variables consisted of repetition-based and duration-based circuit training, while the dependent variables included Body Mass Index (BMI) and fitness level. The population consisted of 89 students of SMK Pelayaran Baruna Pemalang, while the study involved a purposive sample of 55 students. The findings revealed that the circuit training method simultaneously had no significant effect on Body Mass Index, with a significance value of 0.879 > 0.05, whereas the circuit training method demonstrated a simultaneous significant effect on physical fitness, indicated by a significance value of 0.003 < 0.05. The study concludes that repetition-based circuit training is effective in enhancing physical fitness. In addition, there is an interaction between repetition- and duration-based circuit training on Body Mass Index and physical fitness. Future research may further develop other circuit training models to enhance fitness